Exploring the relationship between student engagement and academic achievement in science: A study of junior high school students - Annie Satriani Achwani; Taufik Rahman; Lilit Rusyati (Education and Development Research, 2025)
Academic success, especially in science education, is greatly influenced by student engagement, but its effects vary depending on socioeconomic status and past performance, leaving gaps in how each type of engagement specifically impacts junior high students. According to research, these interactions require more investigation in order to guide focused interventions, fair policies, and instructional strategies that improve student engagement and science proficiency, particularly for diverse student populations. This study investigates the relationship between junior high school scientific achievement and student involvement, with a particular emphasis on the engagement indicators that most accurately predict academic performance. This study uses a correlational research design to quantitatively examine the direction and degree of the association between junior high school students' academic achievement in science and their level of student involvement. Participants in the study were 100 eighth graders (31% male, 69% female) from a public junior high school in Bandung, West Java, Indonesia. There are two instruments used in the study, namely a questionnaire for student engagement and multiple-choice questions through online exams with the Pijar Sekolah application. Since all of the Spearman coefficients were weak and statistically insignificant (p > 0.05), the study found no significant correlation between academic achievement and student engagement (cognitive, behavioural, emotional, or social). These results suggest that engagement-focused therapies should be re-examined, and other indicators of academic performance should be investigated. In order to better understand these dynamics, future research should use longitudinal designs and include other variables (such as self-efficacy and institutional support).